2013
DOI: 10.1007/s11916-013-0348-5
|View full text |Cite
|
Sign up to set email alerts
|

Physiologic Effects of Dry Needling

Abstract: During the past decades, worldwide clinical and scientific interest in dry needling (DN) therapy has grown exponentially. Various clinical effects have been credited to dry needling, but rigorous evidence about its potential physiological mechanisms of actions and effects is still lacking. Research identifying these exact mechanisms of dry needling action is sparse and studies performed in an acupuncture setting do not necessarily apply to DN. The studies of potential effects of DN are reviewed in reference to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
183
0
19

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 255 publications
(208 citation statements)
references
References 54 publications
6
183
0
19
Order By: Relevance
“…Spinally, DN needling has been shown to activate the descending pain modulatory system, which is mediated by a synergic relationship between opioids and non-opioids, including serotonin and norepinephrine [185]. Guo et al found that EDN results in the reciprocal stimulation of β-endorphin containing neurons in the arcuate nucleus (ARC) and periaqueductal grey (PAG) via glutamate transporter-3 [186].…”
Section: The Role Of Spinal Opioids/non-opioids In Dry Needling Mediamentioning
confidence: 99%
“…Spinally, DN needling has been shown to activate the descending pain modulatory system, which is mediated by a synergic relationship between opioids and non-opioids, including serotonin and norepinephrine [185]. Guo et al found that EDN results in the reciprocal stimulation of β-endorphin containing neurons in the arcuate nucleus (ARC) and periaqueductal grey (PAG) via glutamate transporter-3 [186].…”
Section: The Role Of Spinal Opioids/non-opioids In Dry Needling Mediamentioning
confidence: 99%
“…These theories originate from the research performed by Simons and Travell, Gerwin, Shah, and Dommerholt. 10,[12][13][14][15][16][17] Based on the IMS theory, Gunn 18 proposes that the pain from MTrPs is a result of neuropathic pain from the irritation of the spinal nerve root caused by the shortening of the corresponding segmental paravertebral muscles. 13,18 Hypersensitivity then develops in skeletal muscles innervated with the nerve root, leading to the development of MTrPs.…”
Section: Introductionmentioning
confidence: 99%
“…8,[11][12][13]15,16,19,20 Individuals with and without low back pain have demonstrated varied responses in muscle activation following a dry needling intervention to the lumbar multifidi muscles. [21][22][23] Studies investigating the physiological effects of dry needling of the lumbar multifidi muscles in individuals with 22,23 and without low back pain 21 demonstrate changes in nociceptive sensitivity, segmental mobility and motor function following the interventions.…”
Section: Introductionmentioning
confidence: 99%
“…There are several interventions currently adopted to treat trigger points [5] and dry needling is one of the most popular. It is a minimally invasive technique with documented benefits within the physiopathology of trigger points [6]. However, its use in the treatment of latent myofascial trigger points needs further investigation.…”
Section: Introductionmentioning
confidence: 99%